Modeling options for rainwater harvesting developments in a public institution as part of sustainable urban water management solutions - Csete Ákos Kristóf (ACTA CLIMATOLOGICA, 2019)
The water cycle of cities is very different from that of natural areas, and it is characterized by artificial energy flow processes and materials. Due to the high concentration of population, weather extremes in urban areas can cause greater personal and economic damage than in rural areas. Besides extreme amounts of precipitation, which is only one type of extreme weather events, it is important to be prepared for drought and dry periods (which are typical in Szeged and the southern region of the Great Hungarian Plain). During these periods, urban vegetation requires additional irrigation due to the urban artificial environment and the special species composition. This irrigation water basically means potable water resources. It is not a sustainable way to protect potable water resources, therefore any solution that can alleviate this situation is a major improvement. In our study, we modeled a rainwater harvesting system which is established in an elementary school in Szeged. We paid special attention to the quantitative and time distribution properties of the potential precipitation available for the rainwater harvesting system.